2010
DOI: 10.1161/circresaha.110.231985
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Heme Oxygenase-1 and the Multifunctional Transcription Factor Yin Yang 1 in the Inhibition of Intimal Hyperplasia

Abstract: Objective: Because such cell-specific effects are reminiscent of the action of the transcription factor Yin Yang (YY)1, we tested the hypothesis that there is a functional relationship between HO-1 and YY1. Methods and Results: We report that probucol increases the number of YY1؉ cells in rat carotid artery following balloon injury at a time coinciding with increased HO-1 expression. The drug also induces the expression of YY1 mRNA and protein in rat aortic smooth muscle cells (RASMCs) in vitro, as do other kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 52 publications
3
31
0
Order By: Relevance
“…c-Fos is expressed during wound repair (27) and is a prototypic member of the AP-1 transcription factor family (19,32,33) which play an important role in wound healing (3). YY1 is an injury-inducible GLI-Krüppel zinc finger protein (6,30,31). This study is the first to identify functional c-Fos and YY1 binding elements in the PDGF-R-␣ promoter.…”
Section: Discussionmentioning
confidence: 99%
“…c-Fos is expressed during wound repair (27) and is a prototypic member of the AP-1 transcription factor family (19,32,33) which play an important role in wound healing (3). YY1 is an injury-inducible GLI-Krüppel zinc finger protein (6,30,31). This study is the first to identify functional c-Fos and YY1 binding elements in the PDGF-R-␣ promoter.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 We evaluated in vivo effects of LMWF on blood pressure and local blood flow, ex vivo effects on endothelium-dependent vasodilation and eNOS expression, and in vitro effects of LMWF on eNOS phosphorylation in endothelial cells, and compared them with the effects of probucol, a lipidmodifying drug with powerful antioxidant and antiinflammatory properties used for prevention of type 2 diabetes mellitus. [22][23][24] We found that LMWF profoundly protects endothelial function against the complications of diabetes.…”
mentioning
confidence: 85%
“…HMOX1 and CO can induce the transcription factor Yin Yang 1 (YY1) (9) that suppresses SMC proliferation without affecting EC proliferation (138). Up-regulation of YY1 by the HMOX1 inducer probucol was necessary for the inhibition of intimal hyperplasia in a rat model (9). Moreover, overexpression of YY1 can up-regulate HMOX1 expression (9).…”
Section: Dunn Et Almentioning
confidence: 99%
“…For example, hypoxia increases HMOX1 expression in human dermal fibroblasts (127), while hypoxia is associated with decreased HMOX1 expression in human coronary artery EC, human umbilical vein EC, and immortalized human microvascular EC (88,106,119). The findings in human tissues are reminiscent of the tissue-specific effects of HMOX1 induction on cell proliferation, for example, inhibition in SMC (9,42) and stimulation in EC growth (36). By contrast, in rodents, hypoxia increases HMOX1 expression in rat pulmonary aortic EC (83), immortalized mouse EC (55), and rat aortic SMC (92).…”
Section: Dunn Et Almentioning
confidence: 99%
See 1 more Smart Citation